2014
DOI: 10.1186/s40555-014-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding spectra and activity of the freshwater crab Trichodactylus kensleyi (Decapoda: Brachyura: Trichodactylidae) at La Plata basin

Abstract: Background: In inland water systems, it is important to characterize the trophic links in order to identify the 'trophic species' and, from the studies of functional diversity, understand the dynamics of matter and energy in these environments. The aim of this study is to analyze the natural diet of Trichodactylus kensleyi of subtropical rainforest streams and corroborate the temporal variation in the trophic activity during day hours. Results: A total of 15 major taxonomic groups were recognized in gut conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Similarly, studies of trichodactylid crab gut contents have reported the consumption of plant detritus and insect larvae (e.g. Pirela & Rincón, 2013;Williner et al, 2014).…”
Section: Mechanisms Of Leaf Breakdown By Crabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies of trichodactylid crab gut contents have reported the consumption of plant detritus and insect larvae (e.g. Pirela & Rincón, 2013;Williner et al, 2014).…”
Section: Mechanisms Of Leaf Breakdown By Crabsmentioning
confidence: 99%
“…However, there have been some recent feeding ecology studies on trichodactylid crabs in South America (e.g. Pirela & Rincón, 2013;Williner, Carvalho, & Collins, 2014) that have found that crab gut contents predominantly include allochthonous plant material, as well as a wide trophic range of prey items. Costa et al (2016) documented higher survivorship of the caddisfly Triplectides sp.…”
Section: Introductionmentioning
confidence: 99%
“…Ghost shrimps nowadays constitute important components of the normal marine near-shore macro-invertebrate assemblages and also of estuarine environments with high salinity fluctuations ( Dworschak, 2000a ). True freshwater brachyurous crabs constitute nearly 20 % of all known extant crab species in 14 families ( Yeo et al, 2008 ); some of them are able to live inland ( Taylor and Greenaway, 1979; Waltham et al, 2014; Williner et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several biological and ecological aspects of freshwater decapod crustaceans are still scarce in the literature, such as trophic ecology, behavioral ecology, functional diversity, population dynamics studies, sex ratio, reproductive period, size at maturity, population delimitation, and the relation of the species with different environments (Davanso et al 2013;Herrera et al 2013;Sharma & Gupta 2013;Williner et al 2014). Approximately, 20% of brachyurans inhabit fresh waters (Yeo et al 2008), and they can be found on every continent .…”
Section: Introductionmentioning
confidence: 99%